The skillful teacher : on technique, trust, and responsiveness in the classroom - Brookfield, Stephen (Jossey-bass higher and audlt education series, 2015)
"Energize your classrooms with these key techniques for college teachingStudents say the best teachers get them excited about learning, stretch their thinking, and keep them actively involved in class. But with increasingly diverse classrooms and constantly changing technology, each semester throws up new challenges for engaging students.Discover how to keep your teaching, and your students, energized with The Skillful Teacher, a practical guide to effective techniques, approaches, and methods for today's college classrooms. Providing insights, reflections, and advice from his four decades of college teaching, Stephen Brookfield now adapts his successful methods to teaching online, working with diverse student populations, and making classrooms truly inclusive. As well as being completely revised, updated, and rewritten, this edition adds six brand new chapters on: Teaching critical thinking Using play and creativity in the classroom Teaching in teams Helping students take responsibility for learning Teaching about racism Exercising teacher power responsibly Readers will delve into what learning feels like from a student's perspective, as well as absorb the wisdom of veteran college faculty with whom the author has worked. Themes from the bestselling previous editions remain, but are revisited and expanded with the perspective of an additional decade in the classroom. This authoritative guide is now even more comprehensive to better serve teachers looking to improve. Whether you are new to the classroom or are looking to rise to new challenges, The Skillful Teacher will provide answers, expand your repertoire of techniques, and invigorate your teaching and your classrooms"--